BARDAISAN OF EDESSA AND MEMORIES OF CHRISTIAN PERSECUTION IN THE NEAR EAST. (25th June 2019) - ANDRADE, NATHANAEL
Abstract: According to Eusebius, the famous Edessene thinker Bardaisan wrote his work On Fate in a time of persecution and addressed it to a figure named Antoninus ( HE 4.30). It is commonly surmised that this 'Antoninus' was a Roman emperor who sanctioned Christian persecution in some way. But scholars have varied in their interpretations. Some have identified this figure as Caracalla, who visited Edessa in 216–217. But since Eusebius situated Bardaisan's activity in the reign of Marcus Aurelius, he is often deemed to be the Antoninus in question. As this article surmises, the testimony of Eusebius and other late antique authors, like Epiphanius, reflect certain memories both of the integration of Edessa into the Roman provincial system under Caracalla and the social tensions that it raised. But largely due to Eusebius' narrative, late antique authors conceived of Marcus Aurelius as the 'Antoninus' to whom Bardaisan reportedly addressed On Fate and other apologetic work, and they created social memories of Bardaisan as a would-be confessor in a context of persecution.